2020
DOI: 10.1097/md.0000000000021686
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ulcerative colitis-associated colorectal cancer

Abstract: Inflammatory bowel disease is associated with an increased risk of colorectal cancer. The study aims to identify the risk factors for ulcerative colitis-colorectal cancer and to perform a survival curve analysis of the outcome. This retrospective cohort study included 254 patients from March 2016 to October 2017. Age, age at diagnosis, follow-up time, smoking status, and family history of colorectal cancer were analyzed as risk factors for colorectal cancer. The mean patient age was 46.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Previous studies have shown that the main area of colon cancer incidence (25,26). Although recent studies have suggested that patients with UC do not have a particularly high rate of CRC conversion, the prevalence is still very high compared with the general population (27,28). Numerous studies have suggested ethnic differences in the incidence of UC, with most previous statistical studies focusing on European regions (29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the main area of colon cancer incidence (25,26). Although recent studies have suggested that patients with UC do not have a particularly high rate of CRC conversion, the prevalence is still very high compared with the general population (27,28). Numerous studies have suggested ethnic differences in the incidence of UC, with most previous statistical studies focusing on European regions (29).…”
Section: Discussionmentioning
confidence: 99%
“…Those who suffer, have increased mortality with a risk of cancer, blood clots, and primary sclerosing cholangitis. 6 IBD may occur at any age through adolescents to adults irrespective of the sex. Genetic, environmental, and immunological factors contribute in unison toward compromising the intestinal epithelial barrier function increasing the risk of disease.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Symptoms of both CD and UC include intermittent abdominal pain, weight loss, diarrhea, rectal bleeding, fever, and fatigue. Those who suffer, have increased mortality with a risk of cancer, blood clots, and primary sclerosing cholangitis 6 . IBD may occur at any age through adolescents to adults irrespective of the sex.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…IBD consists of two types of idiopathic disorders (Crohn’s disease and ulcerative colitis) which lead to inflammation of the colonic mucosa. The cumulative risk of developing CRC is estimated to be as high as 30% for those with IBD [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%